Curriculum Alignment, Implementation Fidelity, and Outcome Evidence in a Pesantren-Based Intensive English Course: A Discrepancy Evaluation of the Madani Course Program - Muh Junaidi; Ni Nyoman Padmadewi; I G A Lokita Purnamika Utami; Putu Suarcaya (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The Intensive English programs in pesantren often provide rich exposure and strong motivational support, yet their curriculum, implementation, assessment, and documented outcomes may not be systematically aligned. This study evaluated curriculum alignment, implementation fidelity, outcome evidence, and improvement priorities in the four-week Madani Course Program using the five stages of the Discrepancy Evaluation Model (DEM). Methodology: A qualitative evaluative case study involved one program director, one coordinator, four tutors, and twenty-four students. Data were generated through semi-structured interviews, six classroom observations, and analysis of schedules, materials, attendance records, tutor notes, assessment records, and program reports. The evidence was thematically coded, triangulated in student- and program-level evidence matrices, compared with explicit standards, and classified as minor, moderate, or major discrepancies. Main Findings: Triangulated evidence indicated positive perceived and observed outcomes in confidence, participation, routine vocabulary use, self-introduction, and learning discipline. However, moderate discrepancies affected measurable outcomes, curriculum sequencing, tutor preparation, structured modules, target-language use, feedback, monitoring, and reporting. A major product-stage discrepancy remained because comparable diagnostic and final speaking assessments were unavailable; therefore, firm claims about linguistic improvement could not be made. Novelty/Originality of this study: The study contextualizes DEM by integrating communicative pedagogy, formative assessment, and pesantren educational culture into a transparent program-alignment framework. The findings imply that similar residential programs should connect measurable weekly outcomes, tutor preparation, staged language-use policies, comparable speaking tasks, portfolios, and evidence-based reporting.